Cellular elemental stoichiometry of two phytoplankton species, Rhodomonas salina and Teleaulax sp., and the heterotrophic dinoflagellate Oxyrrhis marina - Meunier, Cédric Léo; Schulz, Karoline; Boersma, Maarten; Malzahn, Arne (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2020)
Cellular elemental stoichiometry of two phytoplankton species, Rhodomonas salina and Teleaulax sp., grown in nutrient replete F/2 medium and in P-limited conditions, as well as cellular elemental stoichiometry of the heterotrophic dinoflagellate Oxyrrhis marina fed with these four types of phytoplankton individually.